TiO2 nanotubes incorporated into a glaze-coating ceramic: surface roughness, color, and antibiofilm activity - Picolo, Mayara Zaghi Dal; Andre, Carolina Bosso; Kantovitz, Kamila Rosamilia; Carvalho, Gabriela Luiza Moreira; Costa, Bruna Carolina [UNESP]; Lisboa-Filho, Paulo Noronha [UNESP]; Cavalli, Vanessa (Springer Nature, 2024)
This study evaluated the surface roughness, color change, and antibacterial effect of a ceramic glaze enhanced with TiO2 nanotubes (n-TiO2). n-TiO2 (0, 2, 2.5, and 5 wt%) was added to a ceramic glaze powder, applied to the surface of forty feldspathic ceramic specimens, and sintered. The surface roughness average (Ra) before glaze application (T0) and after glaze crystallization (T1) was measured using a profilometer. The colorimetric alteration was determined by CIEDE2000 (ΔE00) and CIELab (ΔEab), and the whiteness index for dentistry (ΔWID). The antibacterial effect against S. mutans and S. sanguinis was evaluated (CFU/mL). Data were analyzed by two-way repeated-measures ANOVA, followed by the Bonferroni test (α = 0.05). No differences in ΔEab and ΔE00 were observed among groups (p > 0.05), and ΔWID was only affected by 5% n-TiO2. All groups surpassed the perception thresholds of 1.8 (ΔE00) and 2.3 (ΔEab). At T0, no Ra differences were detected among groups (p > 0.05). In T1, Ra decreased (p < 005) compared to T0, but 5% n-TiO2 increased roughness compared to the control group (without n-TiO2). The incorporation of n-TiO2 into the glaze powder did not impair bacteria adhesion, and no differences in biofilm formation were found among the concentrations (p < 0.05). The ceramic covered with a glaze containing 5% n-TiO2 caused minimal interference in the color and roughness with no effect on biofilm formation.
Keywords: Biofilms; Ceramics; Computer-aided design; Titanium dioxide